2013
DOI: 10.1371/journal.pone.0055540
|View full text |Cite
|
Sign up to set email alerts
|

Rapid and Non-Enzymatic In Vitro Retrieval of Tumour Cells from Surgical Specimens

Abstract: The study of tumourigenesis commonly involves the use of established cell lines or single cell suspensions of primary tumours. Standard methods for the generation of short-term tumour cell cultures include the disintegration of tissue based on enzymatic and mechanical stress. Here, we describe a simple and rapid method for the preparation of single cells from primary carcinomas, which is independent of enzymatic treatment and feeder cells. Tumour biopsies are processed to 1 mm3 cubes termed explants, which are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 16 publications
1
13
0
Order By: Relevance
“…With our new intermediate cell line PiCa from our group, we were able to conduct treatment experiments at a larger scale and confirmed current therapy expectations (23). While this might seem like a circumstantial fact, it supports our theory that PiCa cells reflect actual human tumor behavior better than other, more aged and passaged cell lines that underwent numerous passages.…”
Section: Anticancer Researchsupporting
confidence: 76%
See 2 more Smart Citations
“…With our new intermediate cell line PiCa from our group, we were able to conduct treatment experiments at a larger scale and confirmed current therapy expectations (23). While this might seem like a circumstantial fact, it supports our theory that PiCa cells reflect actual human tumor behavior better than other, more aged and passaged cell lines that underwent numerous passages.…”
Section: Anticancer Researchsupporting
confidence: 76%
“…The UPCI-SCC-154 cell line from oropharyngeal HPV-associated cancer was obtained by U. Schoetz (Department of Radiation Oncology, Munich, Germany). The intermediate cell line PiCa originated from our associated workgroup at Großhadern campus (23). Cells were cultured in Dulbecco's modified Eagle's medium (DMEM; Biochrom, Berlin, Germany) supplemented with 10% fetal bovine serum (Gibco Life Technologies, Paisley, UK), 1% penicillin/streptomycin (Biochrom), 1% sodium pyruvate (Biochrom), 1% non-essential amino acids (Biochrom) and 1% L-Glutamine (Gibco Life Technologies).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cell culture and luciferase transduction KPC cells were established from spontaneous KPC tumors that were finely minced using scalpels and directly plated (outgrowth method), without mechanical or enzymatic dissociation as previously described. 41 KPC tumors were obtained from crossing the LSL-Kras-G12D with LSL-p53-R172H and PDX1cre mice (NCI-Frederick) and further backcrossing for >10 times to attain animals with a predominantly C57BL6 background. Cells were maintained in Dulbecco's Modified Eagle's Medium (DMEM) supplemented with 10% fetal bovine serum and 100 U/mL of penicillin/streptomycin (Gibco) at 37 C, 5% CO 2 in a humidified incubator.…”
Section: Methodsmentioning
confidence: 99%
“…[98] Hagemann et al studied formation of spheroids from the PiCa cell line, which was generated from primary carcinoma specimens without enzymatic digestions of single cells. [99,100] Spheroids were grown using two methods-1) the method of hanging droplet, where cell aggregation is promoted by gravitational accumulation of cells in the water-air interface of droplets; and 2) ultra-low attachment plates (ULA), where cells are prevented from attaching to the surface, which leads to cell aggregation. The authors successfully formed spheroids using both methods and demonstrated reduction of spheroid diameter by treating them with cisplatin, 5-fluorouracil (5-FU), or radiation.…”
Section: Dsrt On 3d Cell Culture Modelsmentioning
confidence: 99%